2015
DOI: 10.1007/s10646-015-1585-7
|View full text |Cite
|
Sign up to set email alerts
|

Toxicokinetics of Ag in the terrestrial isopod Porcellionides pruinosus exposed to Ag NPs and AgNO3 via soil and food

Abstract: Soares, Amadeu M.V.M.; Loureiro, Susana. 2016. Toxicokinetics of Ag in the terrestrial isopod Porcellionides pruinosus exposed to Ag NPs and AgNO3 via soil and food. Ecotoxicology, 25 (2). 267-278. 10.1007/s10646-015-1585-7 Contact CEH NORA team at noraceh@ceh.ac.ukThe NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner. Isopods were exposed to contaminated Lufa 2.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 53 publications
(64 reference statements)
0
46
1
Order By: Relevance
“…We found that Fe 0 NP body burdens and BCFs were relatively low in worms, similar to results of other studies and BCFs of Fe 0 NPs in medaka fish. 10,59 The BMFs were smaller than 1 in both waterborne and food-borne Fe 0 NP-exposed worms ( Table 2), indicating that biomagnification effects did not occur in the food-chain structure of E. coli-C. elegans. The biomagnification effects of various metal-based NPs, such as CdSe quantum dots, Au, CeO 2 , and TiO 2 , have been evidenced in several studies.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…We found that Fe 0 NP body burdens and BCFs were relatively low in worms, similar to results of other studies and BCFs of Fe 0 NPs in medaka fish. 10,59 The BMFs were smaller than 1 in both waterborne and food-borne Fe 0 NP-exposed worms ( Table 2), indicating that biomagnification effects did not occur in the food-chain structure of E. coli-C. elegans. The biomagnification effects of various metal-based NPs, such as CdSe quantum dots, Au, CeO 2 , and TiO 2 , have been evidenced in several studies.…”
mentioning
confidence: 98%
“…58 The trends of TBTK estimates were also consistent with a previous study where values of uptake parameters were higher than elimination ones ( Table 2). 59 The uptake constants of waterborne Fe 0 NP-exposed worms were higher than those of food-borne-treated ones, suggesting that Fe 0 NPs accumulated easily in worms via waterborne routes ( Table 2). We found that Fe 0 NP body burdens and BCFs were relatively low in worms, similar to results of other studies and BCFs of Fe 0 NPs in medaka fish.…”
mentioning
confidence: 99%
“…Studies to understand the uptake, kinetics and transformatoin of metal nanoparticles in terrestrial ecosystems usually include the terrestrial isopods [29][30][31]. Terrestrial ispods enable the study of uptake and transformation of metal nanoparticles because of their ability to uptake nanopartiles extensively through the oral route.…”
Section: Introductionmentioning
confidence: 99%
“…Earthworms have macrophage immune cells called coelomocytes, and their viability has previously been shown to be affected by exposure to AgNPs [31]. End-points of toxicity that were assessed in the current thesis include cell viability, intracellular ROS production, reduction in ATP cellular levels, alterations in the integrity of the mitochondrial permeability transition pore opening, and induction of TNF-α [94][95][96][97][98][99]. At the individual level, in vivo responses to AgNP exposures may confirm mechanistic insights derived from in vitro studies, and toxicity end-points commonly studied are survival, growth rate and reproduction (cocoon production).…”
Section: In Vitro -In Vivo Approachmentioning
confidence: 99%
“…Thus, neither particulate nor ionic forms of Ag seemed to be associated with MTs. It is possible that Ag ions are sequestered in the insoluble granules, as was suggested for isopods in which an inert fraction of internalised Ag was assumed after exposure to AgNPs [95] The presumed role of MTs in AgNP toxicity to earthworms is generally based on indirect observations, quantifying this protein in tissues after exposure or looking at gene expression profiles. An interesting approach is by tissue fractionation [90,96], as was done in the current thesis (Chapter 5).…”
Section: Earthworm Tissue Fractionationmentioning
confidence: 99%